Brain-Derived Neurotrophic Factor Participates in Determination of Neuronal Laminar Fate in the Developing Mouse Cerebral Cortex - Fukumitsu, Hidefumi (J Neurosci, 2006)
Lamina formation in the developing cerebral cortex requires precisely regulated generation and migration of the cortical progenitor cells. To test the possible involvement of brain-derived neurotrophic factor (BDNF) in the formation of the cortical lamina, we investigated the effects of BDNF protein and anti-BDNF antibody separately administered into the telencephalic ventricular space of 13.5-d-old mouse embryos. BDNF altered the position, gene-expression properties, and projections of neurons otherwise destined for layer IV to those of neurons for the deeper layers, V and VI, of the cerebral cortex, whereas anti-BDNF antibody changed some of those of neurons of upper layers II/III. Additional analysis revealed that BDNF altered the laminar fate of neurons only if their parent progenitor cells were exposed to it at approximately S-phase and that it hastened the timing of the withdrawal of their daughter neurons from the ventricular proliferating pool by accelerating the completion of S-phase, downregulation of the Pax6 (paired box gene 6) expression, an essential transcription factor for generation of the upper layer neurons, and interkinetic nuclear migration of cortical progenitors in the ventricular zone. These observations suggest that BDNF participates in the processes forming the neuronal laminas in the developing cerebral cortex. BDNF can therefore be counted as one of the key extrinsic factors that regulate the laminar fate of cortical neurons.